INVESTIGATION OF POSSIBLE UNIAXIAL ANISOTROPY IN Co₁₁Zr₂ MAGNETIC PHASE - HIRIAN, R.; PALADE, P.; CIORÎȚĂ, A.; MACAVEI, S.; POP, V. (Studia Universitatis Babeș-Bolyai Physica, 2020)
The Co11Zr2 magnetic phase was obtained by a combination of melting, mechanical milling and high temperature annealing. The structure and magnetic properties of the obtained material were investigated. Even though the samples possessed low coercivity, it was shown that they possess uniaxial anisotropy.